Characterization of vagile fauna associated with suspended mussel farms - Silvestri, Fausto; Bernadochi, Ligia Coletti; Rodrigues, Carina Waiteman; Shimabukuro, Mauricio; Costa, Paulo Marcio Santos; Turra, Alexander (Arquivos de Ciências do Mar, 2019)
Mussel farms provide shelter and food for a wide variety of organisms making a favorable environment for the establishment of biological populations. However, the presence of these organisms in mussel farms generates ecological and zootechnical consequences, both positive and negative. In the present study, we performed the first characterization of the vagile fauna associated to small brown mussels Perna perna (L.1758) farms in southeastern Brazil. This represents an important contribution to understanding the effects of the presence of these organisms both in the mussel farms and in the environment that they are inserted. During one year, 41.082 organisms were identified, from a total of 109 different taxa that were directly associated with the strings of mussels. The community structure of the vagile varied throughout the study, indicating the dominance of amphipods in all periods analyzed. Therefore, results indicated that the suspended mussel culture performed in a coastal area played a strategic role to the attraction and refuge of vagile species.